PELATIHAN PENGEMBANGAN LITERASI DAN NUMERASI TERHADAP GURU MTSS NURUL QURAN KABUPATEN BIREUEN PROVINSI ACEH - Misnawati Misnawati; Rahmi Hayati; Zuraini Zuraini; Eli Nofriati; Yessi Kartika (LPPM Universitas Al Muslim, 2023)
Literacy and numeracy development are two important components in education that help individuals acquire the skills of reading, writing, understanding information, as well as abilities in mathematics and understanding numbers. These two skills are the basis for success in various aspects of life, including further education, career, and active participation in society. It is important to create an educational environment that supports literacy and numeracy development. The method for implementing community service activities went through several stages, namely pre-preparation, preparation, implementation and closing. Teachers have a key role in teaching and guiding students to develop these skills. In addition, the integration of literacy and numeracy in various subjects and activities outside the classroom helps link these skills to real life. Thus, developing literacy and numeracy is a continuous process that involves collaboration between schools, families and communities to create individuals who have a strong foundation of skills for success in life. Evaluation of activity implementation and sustainability is planned to involve the Almuslim University Research and Community Service Institute. The evaluation carried out by the community service team is the extent to which coaching and mentoring activities for students have had a good impact.